The effects of undernutrition and dexamethasone treatment on cultured rat neonatal cardiomyocytes - Austin, Ruth Marie (2010)
It is well-established that undernutrition during pregnancy increases offspring’s risk of disease in later life. Studies have found that maternal protein restriction during rodent gestation programmes premature hypertrophic growth and decreased mitotic index of cardiomyocytes, as well as impaired contractile ability of the heart. All of these are predisposing factors to cardiovascular disease. To date, few studies have focused on the underlying mechanisms that lead to such alterations in the structure and function of the cardiovascular system. This study aimed to investigate if protein deficiency during gestation impacts upon cardiomyocyte proliferation, and glucose uptake and transport in vitro, and if programming effects can be demonstrated in culture. Methods. Trial 1: Ten pregnant wistar rats were fed either a control or low protein (MLP) diet throughout gestation. Pups were culled on the day of birth and hearts were taken to isolate cardiomyocytes. After 10 days in culture (baseline) some cardiomyocytes were treated with 100nM and 10μM of dexamethasone (Dex) for 48 hours (Day 2). Both untreated and Dex treated cultures were analysed for proliferation and differentiation rates, and glucose uptake. Trial 2: Gestational diet and culturing of cardiomyocyte cells was the same as in trial one. Cultures were treated with 10nM and 100nM Dex and analysed at the same time points for proliferation and differentiation rates, cell apoptosis and mRNA expression of glucose transporters. Results. In trial one, MLP diet increased day 2 binucleation. High concentrations of Dex increased insulin stimulated glucose uptake in MLP neonatal cardiomyocytes indicating they had an increased sensitivity to glucocorticoids. In trial two, Dex treatment decreased expression of GLUT 4 and increased expression of glucocorticoid receptor (GR) mRNA. Conclusion. Results indicate possible remodelling of the heart in rat offspring exposed to MLP diet in utero, but it remains unclear as to what mechanism underpins MLP cultures increased sensitivity to glucocorticoids. There were some similarities to the findings of in vivo studies, but responses varied between trials. This indicates that cell culture is unlikely to become a viable alternative model, but it is a useful tool for exploring focused mechanisms of fetal programming.